Обыкновенная история - Гончаров Иван Александрович (Пушкинская библиотека, 2000)
Экземпляры: аб. (2000) / Инвентарный номер: 42450 / Цена: / Сис.шифр: 84(2Рос=Рус)1-4 / Авт.знак: Г 65 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)1-4